Descriptive Analysis Of The Physical Condition Of Female Pencak Silat Athletes From South Sulawesi Province - Muhammad Rizky Alfarizi; Muslim Bin Ilyas (Indonesian Journal of Physical Activity, 2026)
Physical condition is a fundamental factor in supporting the performance and achievement of pencak silat athletes. This study aimed to describe the physical condition of female pencak silat athletes from South Sulawesi Province who participated in the National Student Sports Week. A quantitative descriptive method was employed, involving 10 female athletes as research subjects. The assessment instruments included tests of speed, agility, strength, power, and aerobic endurance (VO₂Max). Data were analyzed using descriptive statistics, including minimum and maximum values, mean, standard deviation, and the distribution of physical condition categories. The results indicated that speed and agility showed relatively low variability among athletes, whereas strength and VO₂Max exhibited higher variability. The categorical analysis revealed that 10% of athletes were classified as good, 40% as sufficient, and 50% as poor. These findings suggest that the overall physical condition of female pencak silat athletes in South Sulawesi Province has not yet reached an optimal level. Therefore, the implementation of a more structured, targeted, and sport-specific training program is necessary to improve athletes’ physical readiness and performance.